Current status of annelid phylogeny - Weigert, Anne; Bleidorn, Christoph (Organisms Diversity & Evolution, 2016)
Annelida is an ecologically and morphologically diverse phylum within the Lophotrochozoa whose members occupy a wide range of environments and show diverse life styles. The phylogeny of this group comprising more than 17,000 species remained controversial for a long time. By using next-generation sequencing and phylogenomic analyses of huge data matrices, it was finally possible to reach a well-supported and resolved annelid backbone tree. Most annelid diversity is comprised in two reciprocal monophyletic groups, Sedentaria and Errantia, which are named after the predominant life style of their members. Errantia include Aciculata (Phyllodocida?+?Eunicida) and Protodriliformia, which is a taxon of interstitial polychaetes. Sedentaria comprise most of the polychaete families formerly classified as Canalipalpata or Scolecida, as well as the Clitellata. Six taxa branch as a basal grade outside of this major radiation: Oweniidae, Magelonidae, Chaetopteridae, Sipuncula, Amphinomida, and Lobatocerebrum. Oweniidae and Magelonidae form a monophyletic group which we name Palaeoannelida, which constitutes the sister taxon of the remaining annelids. The early splits of annelid phylogeny date back to the Cambrian. The new annelid phylogeny highlights the variability and lability of annelid body plans, and many instances of simplifications of body plan as adaptations to new life styles can be found. Therefore, annelids will be an appropriate model to understand major transitions in the evolution of Bilateria in general. Evolutionary developmental studies are one way to investigate macroevolutionary transition in annelids. We briefly summarize the state of developmental model organisms in Annelida and also propose new candidates on the background of the phylogeny.
World Polychaeta Database (WPolyDb)